High-efficient catalytic reduction of 4-nitrophenol based on reusable Ag nanoparticles/graphene-loading loofah sponge hybrid. (30th May 2018) - Liu, Y Y; Zhao, Y H; Zhou, Y; Guo, X L; Chen, Z T; Zhang, W J; Zhang, Y; Chen, J; Wang, Z M; Sun, L T; Zhang, T
Abstract: Noble metal nanoparticles (NPs) such as Au and Ag have shown many applications in the field of catalysis, sensing etc. due to their excellent photoelectric properties. But agglomeration and a low recovery rate are big problems for their applications. In this research, a novel Ag NPs/graphene (reduced graphene oxide)-loading loofah sponge (Ag NPs/RGO-LS) was synthesized through a one-step reduction method. Where the RGO is used as a nano-support with the high specific surface area and the high conductivity to prevent the agglomeration of Ag NPs and provide a conductive layer. The natural, green, low-cost and high-yield LS is designed as a macro-support to reduce the loss of Ag NPs during recycling. The as-prepared Ag NPs/RGO-LS is stable, uniform, and exhibits high efficiency and reusability in the catalytic reduction of 4-nitrophenol (4-NP) with a high rate constant of 1.893 min −1 as well as an average conversion of 98% in 6 min during five cycles. The results have not only paved the way for the wide application of Ag NPs but also provide a new road for the application of other metal NPs.